Giant bronchopleural fistula and empyema in a tuberculosis patient with diabetes mellitus: Vista from a high tuberculosis burden country in Southeast Asia - Yanti, Budi; Hadi, Saiful; Harrika, Fenny; Shehzad, Aamir (Narra Sains Indonesia, 2022)
Bronchopleural fistula is a pathological tract between the bronchial tree and the pleural space, which can be life-threatening due to tension pneumothorax. It is a rare complication in tuberculosis cases with highly variable in clinical manifestations and persistent air leaks which might lead to complications such as empyema. Herein, we present a tuberculosis and diabetic patient complicated with giant bronchopleural fistula and empyema. A 48-year-old man presented with shortness of breath for two weeks and cough with phlegm for two months. The patient was a smoker with severe Brinkman Index and diabetes. Physical examination revealed hyper resonant percussion and vesicular diminished on the left hemithorax. Laboratory results indicated the patient had anemia, leukocytosis, and hypoalbuminemia. GeneXpert sputum confirmed the presence of Mycobacterium tuberculosis and chest X-ray indicated a collapsed left lung. The patient was diagnosed with left secondary spontaneous pneumothorax, pulmonary tuberculosis, and diabetes. The patient was treated with chest tube drainage and anti-tuberculosis drugs. There was no improvement based on serial chest X-ray, and empyema appeared from the chest tube. CT-scan showed tuberculosis lesion, the collapsed of the left lung and fistula in segments 7-8 inferior lobe. Exploratory thoracostomy was performed, in which a giant bronchopleural fistula was detected and then repaired with BioGlue surgical adhesive. Unfortunately, the thoracostomy led to extensive subcutaneous emphysema and was treated by cervical mediastinotomy. The drainage was unable to be removed, and the patient was discharged with Heimlich-type drainage valves on day 28 of treatment. The empyema fluid was cultured and revealed Staphylococcus haemolyticus. This case highlights that tuberculosis could cause a bronchopleural fistula and empyema may occur secondary to late diagnosis that needs immediate surgery.